Tunable dual-wavelength Er3+-doped fibre laser based on a single multimode interference filter. (17th October 2018) - Li, N; Cui, L H; Liu, J X; Jia, Z X; Kang, Z; Dai, Z W; Zhu, F; Huang, K; Wang, F; Qin, G S; Qin, W P
Abstract: We report a dual-wavelength erbium-doped fiber laser (EDFL) with a tunable wavelength spacing from ~9 to 58 nm based on a single multimode interference filter (MMIF). The MMIF has a simple structure of single mode fiber (SMF)-multimode fiber-SMF and two main transmission peaks at 1537 and 1565 nm, which are located in the gain spectrum of the EDF. The wavelength spacings of these two transmission peaks were tuned from 7.8 to 58.5 nm, owing to the multimode interference effect by mechanically bending the MMIF. By adding the MMIF into the EDFL cavity, dual-wavelength lasers were obtained and the corresponding wavelength spacing was tuned from 9 to 58 nm by adjusting the MMIF. To the best of our knowledge, this is the first time an all fiber dual-wavelength EDFL with a tunable wavelength spacing using a curved MMIF has been reported.